(untitled) (Bangladesh Journal of Plant Taxonomy, 2020)
Brassica tournefortii Gouan. (family Brassicaceae) is one of the five species in the Egyptian flora. Its populations showed notable morpho-plasticity with taxonomic debates, which were not yet resolved. The current study was carried out to assess the species morpho-plasticity and its molecular identity based on ISSR. The study was applied to 27 herbarium and fresh populations, representing all the species distribution ranges in Egypt. The taxonomic revision included 70 morphological characters, revealed five distinct Forms (1-5), radical leaf, and fruit provided the major distinguishable traits among the studied 70 morphological characters based on them the morphologic key is provided to delimit these forms. The pollen grain features using SEM are a pioneer at the infra-specific level, two shapes observed the subprolate (Forms 1& 3) and prolate (Forms 2, 4 & 5). Furthermore, the exine micro-features possess taxonomic value at the infraspecific level. The cluster analysis based on ISSR data revealed two clusters congruent to those developed by morphological and pollen traits. The ISSR results indicated that the species morpho-plasticity is genetically controlled. The study highlights the importance of the multidisciplinary approach to assess the taxonomic identity at the infra-specific level, for the auto-taxonomy of morpho-plastic species. Bangladesh J. Plant Taxon. 27(2): 233-250, 2020 (December)